2020
DOI: 10.1111/bjet.12935
|View full text |Cite
|
Sign up to set email alerts
|

Escape boxes: Bringing escape room experience into the classroom

Abstract: In this paper, we present an escape box as a means to introduce the escape room concept into classrooms. Recreational escape rooms have inspired teachers all over the world to adapt the popular entertainment activity for education. Escape rooms are problem‐based and time‐constrained, requiring active and collaborative participants, a setting that teachers want to achieve in their classroom to promote learning. This paper explores the adaptation of the escape room concept into educational escape game boxes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 24 publications
0
55
1
11
Order By: Relevance
“…At a higher level of specificity, the gender variable has only influenced students' motivation and autonomy, as other studies reveal [68,69]. It has been found that women are more motivated and show a higher level of learning anxiety, in analogy with other works [70].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…At a higher level of specificity, the gender variable has only influenced students' motivation and autonomy, as other studies reveal [68,69]. It has been found that women are more motivated and show a higher level of learning anxiety, in analogy with other works [70].…”
Section: Discussionmentioning
confidence: 71%
“…Studies on the implementation of the gamification and Escape Rooms reveal great benefits both in the teaching process [20,22], and in various indicators related to learning [25,27,55]. The latter have to do with an improvement in problem solving [26], in the interaction and collaboration between the people involved [27,28], in activation and attitude [53,57], in motivation [29,52,66] in satisfaction with the environment generated and the task to be carried out [54], and autonomy of students [33,68,69], as well as the results and academic performance achieved [38,64], among the indicators more outstandingly reflected in impact studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some educational escape rooms design guidelines are available in literature [31,32], lacking-in some cases-scientific references supporting such guidelines. Literature has plenty of "false" escape rooms [33,34]: players are accompanied by the teacher [13], or the escape room experience is reduced to "opening a box" [35] during a conventional lecture. Indeed, in these approaches, a player does not have to escape from any room.…”
Section: Design Criteriamentioning
confidence: 99%
“…Once the problem is over, he continues working on it, showing productive disposition (31) and exploring new possibilities by modifying the problem (32). Exploration with different objects allows him to conclude that "objects are heavy"-even "nothing" is heavy-showing a process of generalization (35), which is communicated (33) to his peers. This process of generalization and idealization is hampered by the cognitive limitations of the student at the time of learning (see interview after transcription).…”
Section: Mathematical Objects and Processesmentioning
confidence: 99%
“…The proportion of recreational videogame players among students has steadily increased over time (Prensky, 2001) and this population is expected to find interactive, openended instruction more resonant with their learning style than the classical methods based on unilateral expositions of information. A number of successfully implemented instructional methods incorporating games serves as a testimony to the actuality of interactive, inherently playful education (Gorgen et al, 2020;Liuta et al, 2019;Veldkamp et al, 2020), especially for today's student cohorts heavily influenced by the videogame culture.…”
Section: Results Of the Surveysmentioning
confidence: 99%